Digital imagery via online repository for museums and art galleries in Malaysia / Inda Murni Hairul Anuar - Hairul Anuar, Inda Murni (2016)
The harmony in Malaysia was formulated based on the history, culture and tradition, which contributed to the shaping of a significant heritage. Museums and galleries are responsible for collecting, conserving, preserving and exhibiting their collections to the public. Indeed, the new track of internet technology introduced website as a new vehicle for sharing vital information. Significantly, most developed countries offer upto- date activity, exhibition, and programs and also free access to their collections via online. The web content of museum and gallery in Malaysia however, is random, limited and insufficient in visual data within Malaysian context. The objectives of this study therefore, are to examine the current museums and galleries' websites of selected Developed, ASEAN countries and Malaysia, then finally, to propose a new web layout for good practice for museum and gallery in Malaysia. The approach began with observation through virtual approach. From this, selected samples which are associated with the appropriate model that is in line with Malaysia's context were chosen. Next, the cultural heritage institution that handles their exhibited collections were visited. Interviews were then, conducted with curators and the visitors of museum and galleries. This study concludes; nomenclature, quality and quantity conflicts, opinion divergence and web content. The area of the study could also be expanded by collaborating with available online platform such as Google Art Project to enhance online view. To sum up, this study hopes to contribute in the development of the artefact's value among the consumer and the academicians.